Laboratory Professionals in Africa : The Backbone of Quality Diagnostics - Schneidman, Miriam; Dacombe, Russell J.; Carter, Jane (World Bank, Washington, DC, 2015)
Laboratories have historically been under supported in developing country health systems resulting in poor quality diagnosis and inadequate disease surveillance. Laboratory professionals are predominantly male with relatively limited female labor participation, with potential gender based barriers to advancement. The focus on communicable diseases has meant that funding for broader public health laboratory services has been relatively neglected. In this paper the authors present a number of strategies to address these problems based on the outcomes from a literature review and case studies conducted in four African countries. Improved registration and human resource planning are required to establish the scale of the problem and to develop country specific strategies to address skills shortages. More high quality pre-service training is needed to supply the service with suitably skilled professional staff to address the current deficit. Innovative in-service training is essential to maintain competence and collaboration is required with the private sector to utilize their expertise. A clear career structure with transparent promotional opportunities is required to recruit and retain staff in the public sector. The establishment of suitable work environments and regulatory and representative bodies will also support recruitment and retention as well as enhance quality. It is also clear that this cadre has been underrepresented in human resources for health research and more activity in this area will lead to greater understanding of the problems and provide more potential solutions.